Experience of Performing Systemic-to-Pulmonary Artery Shunt in Patients with Univentricular Heart Physiology and Depleted Pulmonary Blood Flow - Imanov, Elnur; Dziuryi, Ivan V.; Truba, Iaroslav P.; Golovenko, Oleksandr S. (Ukrainian Journal of Cardiovascular Surgery, 2024)
Among patients with congenital heart disease diagnosed in infancy, 7.7% of infants have anatomical variants with functional single ventricle physiology which is often accompanied by depleted pulmonary blood flow. The type of these defects is clinically associated with cyanosis, in most cases caused not by mixing of blood at the level of the heart chambers, but by the presence of ductal-dependent pulmonary blood flow, which requires urgent surgical intervention. The aim. To evaluate the immediate and long-term outcomes of hemodynamic correction in patients with single-ventricle heart physiology with depleted pulmonary blood flow. Materials and methods. In the period from 2010 to 2022, 114 patients with reduced pulmonary blood flow underwent systemic-pulmonary anastomosis at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. Among these, 64 patients had biventricular circulation and subsequently underwent radical correction. The other 50 patients had single-ventricular heart physiology and underwent placement of systemic-pulmonary anastomosis as the first stage of the hemodynamic strategy according to Fontaine, so their data became the main material of this study. Results. Hospital mortality after systemic-pulmonary anastomosis was 8% (4 patients). An uncomplicated course of the early postoperative period was observed in 38 (76%) patients, and 16 complications were observed in the remaining 12 (24%) patients. The median follow-up period was 40 [3; 160] months. During the follow-up period, 2 (4.3%) patients died due to anastomosis thrombosis as a result of self-discontinuation of anticoagulant therapy, 3 (6.5%) patients were lost to follow-up and did not come for examination. The second stage of hemodynamic correction in the form of bidirectional cavopulmonary anastomosis was performed in 41 (82%) patients of the study group. Conclusions. Patients with single-ventricular heart physiology with depleted pulmonary blood flow are a group of extremely complex children who require an individual approach at all stages of hemodynamic correction, and early diagnosis and palliative systemic-pulmonary anastomosis continues to be a reliable alternative for these children, despite the fact that mortality after the first stage remains quite high.